2010
DOI: 10.1029/2010ja015596
|View full text |Cite
|
Sign up to set email alerts
|

Medium‐scale equatorial plasma irregularities observed by Coupled Ion‐Neutral Dynamics Investigation sensors aboard the Communication Navigation Outage Forecast System in a prolonged solar minimum

Abstract: [1] The distribution of medium-scale irregularities in the total ion density at the equator is investigated. In the scale size range between 10 and 400 km, it is found that, as expected, these irregularities preferentially appear near 2100 local time (LT) in longitude regions that are selected by season according to an alignment between the magnetic meridian and the sunset terminator. However, these irregularities have a maximum occurrence frequency in the postmidnight sector and do not conform to the expected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 33 publications
6
55
0
Order By: Relevance
“…The N/N distributions in the second column show irregularities over a significantly larger local time and longitudinal range than for N. The distribution for December 2008 is consistent with a similar plot by Heelis et al (2010) that used a running mean over 400 km to determine N/N. Immediately after sunset, the distribution follows N ; however, it quickly expands westward into an area with positive magnetic declination.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The N/N distributions in the second column show irregularities over a significantly larger local time and longitudinal range than for N. The distribution for December 2008 is consistent with a similar plot by Heelis et al (2010) that used a running mean over 400 km to determine N/N. Immediately after sunset, the distribution follows N ; however, it quickly expands westward into an area with positive magnetic declination.…”
Section: Resultssupporting
confidence: 78%
“…The gradient in conductivity across the terminator has an effect on the magnitude of the fringing field from the F region dynamo that leads to the PRE (Abdu et al, 1981;Eccles, 1998). Numerous satellite investigations 422 R. A. Stoneback and R. A. Heelis: Ion drift irregularities (Kil and Heelis, 1998a;Hei et al, 2005;Gentile et al, 2006;Su et al, 2006;Stolle et al, 2008;Kil et al, 2009;Heelis et al, 2010;Dymond, 2012) have shown that a component of the seasonal and longitudinal variations in irregularity occurrence may be explained by the alignment of the terminator and magnetic field (Tsunoda, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The result roughly agrees with the proposed concept, that is, high occurrence in northern summer (winter) in a longitude sector of −30° to 120° (180° to 300°) where the magnetic equator locates in the Northern (Southern) Hemisphere. Heelis et al [2010] suggested that the seasonal variation of the irregularity occurrence is influenced by seeding from tropospheric sources, and responds to the proximity of the Intertropical Convergence Zone (ITCZ) to the magnetic equator. Tsunoda [2010] has also proposed the importance of seeding from ITCZ to understand the occurrence of ESF during solstices.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in the postsunset sector, great magnetic storms are known to produce large-scale and deep depletions at solar maximum (Greenspan et al, 1991;Kil et al, 2006). The average depletion amplitude is significantly smaller than that commonly observed during solar maximum years 1989 and 1991 under magnetically disturbed conditions in the evening sector (Huang et al, 2001) and in some cases of the deep solar minimum period of 2008 near dawn (Burke et al, 2009;de La Beaujardière et al, 2009;Heelis et al, 2010;Huang et al, 2011Huang et al, , 2012 when there were detected depletions within which the plasma density is reduced by more than three orders of magnitude over several thousands of kilometers in longitude.…”
Section: Discussionmentioning
confidence: 73%
“…The plasma density inside the depletions can be decreased by tens of percent to more than 3 orders of magnitude with respect to the background plasma density (e.g., Kil and Heelis, 1998;de La Beaujardière et al, 2009;Woodman, 2009). There have been many investigations of the morphology of plasma bubbles in the upper ionosphere using in-situ satellite data (e.g., Burke et al, 1979;Watanabe and Oya, 1986;Kil and Heelis, 1998;McClure et al, 1998;Huang et al, 2001Huang et al, , 2002Burke et al, 2004;Kil et al, 2006;Hei et al, 2005;Su et al, 2006;Heelis et al, 2010;Huang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%